Numerical simulation of welding fume lung dosimetry - Zhao, Jianan; Feng, Yu; Bezerra, Marcio; Wang, Jun; Sperry, Ted (Journal of aerosol science, 2019)
Exposures to airborne particles and toxic gases generated by welding fabrication activities will potentially lead to various diseases. Accurate information on the transport and deposition of such aerosols in the respiratory system is critically needed for precise health risk assessments. To address the data demand mentioned above, a multiscale computational fluid-particle dynamics (CFPD) model was developed in this study. Specifically, a virtual fabrication shop was integrated with a virtual human in the numerical model to evaluate the effects of ventilation condition, particle size, and gas species on the lung uptakes of those welding fume particles and gases. Welding fume particle and gases transmission, transport, and deposition have been simulated and analyzed starting from the emission source to the subject-specific human respiratory system via oral inhalation. Spherical iron particles with diameters of 100, 190, and 830 nm were simulated. The transport and absorption of NOx and CO were predicted too. Steady-state inhalation with 11.87 L/min was applied with two different air filter ventilation conditions. The numerical results indicate that the ventilation condition can significantly influence welding gas transport and deposition. The pulmonary gas absorption rate is much higher at poor ventilation conditions. The air-tissue absorption coefficient is another crucial factor that can impact pulmonary gas absorption. The total particle deposition fractions (TDFs) from mouth/nose to generation 6 (G6) are less than 18.0%, and particles mostly deposit in the oral cavity. Regional and local particle deposition data demonstrate that particles tend to enter the two upper lobes more than the other three lobes. In summary, this study paves the way to build a personalized in silico tool based on CFPD models for noninvasive precise health risk assessments associated with different welding activities. •A CFPD based multiscale model is developed for welding fume lung dosimetry estimation.•Welding fume particles tend to enter the two upper lobes more than the other three lobes in the subject-specific respiratory system via mouth inhalation.•Key parameters that can significantly influence welding fume lung dosimetry are determined.